Ticks (Ixodida: Argasidae, Ixodidae) of Brazil: Updated species checklist and taxonomic keys - Dantas-Torres, Filipe; Martins, Thiago Fernandes; Murioz-Leal, Sebastian; Onofrio, Valeria Castilho; Barros-Battesti, Darci Moraes [UNESP] (Elsevier B.V., 2019)
Ticks are ectoparasites of great medical and veterinary significance in the neotropical region. In Brazil, they are responsible for enormous economic losses to the livestock industry and also for considerable morbidity and mortality in companion animals and humans. Therefore, recognizing the identity of a given species is important, not only from a biodiversity perspective, but also from the medical and veterinary standpoints. The Brazilian tick fauna is one of the most diverse and well-studied in the neotropical region. In the past few years, several new species were discovered and/or recorded for the first time in this country. The main objectives of this study were to provide an updated list of tick species occurring in Brazil and taxonomic keys for their identification. The updated list of Brazilian ticks includes 70 species, 47 in the family Ixodidae and 23 in the family Argasidae. The genera Amblyomma (32 spp.) and Ornithodoros (18 spp.) are the most representative. Updated taxonomic keys for the identification of ticks of Brazil are provided. Finally, the medico-veterinary significance of ticks occurring in this country is briefly discussed.
Keywords: Ticks; Taxonomy; Checklist; Morphological keys; Brazil